ON THE BEHAVIOUR OF SOME PROBABILISTIC CHARACTERISTICS OF THE OUTPUT OF MULTIDIMENSIONAL RANDOM WALK FROM EXPANDING SETS - Gafurov M. U. (American Journals Publishing, 2023)
This paper establishes an analog of the well-known theorem of P. J. Bickel and J. A. Yahav on the number of exits of a multidimensional random walk from expanding sets. This theorem and related problems are carried forward for the moment of the first exit.
Keywords: Multidimensional random walk; expanding sets; moment of the first exit; number of exits.